Implementing Restorative Justice in Criminal Case Resolution: A Socio-Legal Research - Dona, Fery; Ariyani, Evi; Junaidi, Junaidi; Zahriani, Luthfiana; Fattaah, Abdul (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This socio-legal research investigates the accountability of criminal offenders and explores the implementation of restorative justice as an alternative framework for resolving criminal cases. Restorative justice, an emerging paradigm in the legal domain, prioritizes reconciliation and resolution over traditional punitive approaches. Law enforcement agencies, particularly the police and prosecutors, are pivotal to its application. This study aims to evaluate the practice of restorative justice in criminal case resolutions at the Sukoharjo Police Department and the Sukoharjo Prosecutor's Office. Adopting an empirical legal research methodology, data collection involved primary and secondary sources through interviews and document analysis. The qualitative data were analyzed using an interactive model to identify patterns and derive insights. The findings reveal that both the Sukoharjo Police and the Prosecutor's Office have incorporated restorative justice within their legal frameworks, albeit with notable differences in legal foundations and procedural approaches. The Sukoharjo Police exhibited a higher frequency of employing restorative justice compared to the Prosecutor's Office, indicating variability in institutional adoption and execution. These findings illuminate the diverse practices and challenges associated with integrating restorative justice into Indonesia's legal system. The study underscores the approach’s potential to enhance justice administration while identifying critical areas for institutional improvement and policy refinement.